2022
DOI: 10.7160/eriesj.2022.150204
|View full text |Cite
|
Sign up to set email alerts
|

Internet Addiction in University Students – Czech study

Abstract: The main purpose of the presented study is to explore the existing risk of Internet addiction for undergraduate students of Czech universities. The research was conducted as quantitative research; a CIAS-R questionnaire was applied. The data were collected in the years just before the Covid-19 pandemic (between October 2019 and March 2020). 3,366 respondents (2,151 females and 1,215 males) participated in our questionnaire survey. The average CIAS-R score achieved by our respondents was 44 points. It equals 6%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…In both samples, females scored better in academic performance, which is a typical trend [82-84]. Males were more at risk of technology addiction than females in the Czech sample, which is congruent with the survey ndings before COVID-19 pandemics [39].…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In both samples, females scored better in academic performance, which is a typical trend [82-84]. Males were more at risk of technology addiction than females in the Czech sample, which is congruent with the survey ndings before COVID-19 pandemics [39].…”
Section: Discussionsupporting
confidence: 78%
“…Moreover, there is only a very limited amount of research in some demographic areas, e.g., in the Czech Republic. One prevalence study was carried out in undergraduate students, focused on internet addiction [39], and one intervention study found a positive effect of combined chamber REST interventions on problematic smartphone usage and mental health of female students [40]. Furthermore, one pilot intercultural study compared results from Czech and Chinese university students and found that Czech students manifested greater rumination and perceived stress, and Chinese students showed greater mobile phone addiction [41].…”
Section: Review Of Current Evidence On This Study Topicmentioning
confidence: 99%
See 1 more Smart Citation
“…Technological addictions are part of non-toxic addictions and constitute addictive processes that develop through overuse and inappropriate use of what the internet offers, such as videos, video games and social networks [2,6]. Technology addiction is characterized by salience, mood changes, tolerance (the need to use longer), depression and irritability when technology is not used, interpersonal conflicts and relapse [4,7].…”
Section: Main Points;mentioning
confidence: 99%
“…It is defined as an uncontrollable preoccupation or strong impulse to use the internet, leading to psychological distress (Weinstein & Lejoyeux, 2010 ). Besides, internet addiction is denoted as behavioral or non-drug addiction (Milková et al, 2022 ; Vacek & Vondrackova, 2014 ; Zou et al, 2017 ). Global estimates reveal around 4.6 billion internet users as of 2021 (Kemp, 2021 ).…”
Section: Introductionmentioning
confidence: 99%